ANALISIS MULTIVARIAT PENGARUH KONTROL DIRI DAN TEKNOLOGI DIGITAL TERHADAP PERILAKU INTERAKSI SOSIAL DAN KUALITAS HUBUNGAN SOSIAL - Ghareta Vanessa; Karina Ariyani; Sifa Zulfa Azizah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of digital technology use on Social Interaction Behavior and the Quality of Social Relationships in the digital era. The research employs a quantitative research design using a survey method. Data were collected from 76 respondents who are active users of smartphones and social media through an online questionnaire using a Likert scale. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software to examine the relationships among variables. The independent variables in this study are Self-Control, Fear of Missing Out (FoMO), and Smartphone Addiction, while the dependent variables consist of Social Interaction Behavior and Quality of Social Relationships. The results indicate that Self-Control has a significant positive influence on Social Interaction Behavior and the Quality of Social Relationships. Conversely, FoMO and Smartphone Addiction do not show significant effects on Social Interaction Behavior or relationship quality. Furthermore, Social Interaction Behavior is found to hAVE a significant effect on the Quality of Social Relationships. These findings suggest that individual psychological factors, particularly Self-Control, play a more important role than technological dependence in shaping healthy social interactions. This study concludes that strengthening Self-Control in technology usage is essential to maintaining effective social interactions and improving the Quality of Social Relationships in the digital era.